(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
Currently, men’s oncology occupies an important place in medicine, because cancer is one of the leading causes of death among men. The most common oncological diseases among men are prostate cancer and lung cancer. Prostate cancer mostly occurs in men over 50 years of age and progresses gradually. As a rule, this disease passes at an early stage almost without symptoms, which makes it difficult to make a diagnosis in time. And lung cancer is one of the most common and most dangerous tumors, not only in men but in the world as a whole. Mainly smoking, environmental factors and work in harmful industries play an important role in the development of this disease. This article discusses the causes, clinical signs, diagnosis and treatment methods of prostate and lung cancer. At the same time, the importance of prevention, early detection and modern methods of treatment of these types of diseases is highlighted. The main goals of the article are to raise awareness for oncology of men, to promote preventive and healthy lifestyles.